2019
DOI: 10.1121/1.5101632
|View full text |Cite
|
Sign up to set email alerts
|

Automated Mandarin tone classification using deep neural networks trained on a large speech dataset

Abstract: A tonal language is one in which the speaker’s intonation modifies the meaning of a word. In this work, we perform a rigorous analysis of intonation changes, or pitch contours, produced by native Mandarin speakers to predict the tone-contour type. Pitch contours are estimated using a number of different methods, also measuring each contour’s Mel-Frequency Cepstral Coefficients (MFCCs). The dataset used was autonomously generated from the Aishell open-source Mandarin speech corpus. Each sample was aligned with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…While the focus of the present study was individual tone production, that model was not suitable in our case. More recently, newly developed artificial intelligence methods were used to classify Mandarin tones [32], [34]. Chen et al used a CNN model based on MFCC to classify tones that produced by normal-hearing children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the focus of the present study was individual tone production, that model was not suitable in our case. More recently, newly developed artificial intelligence methods were used to classify Mandarin tones [32], [34]. Chen et al used a CNN model based on MFCC to classify tones that produced by normal-hearing children.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies also showed that ANNs were able to classify tones well in Mandarin Chinese [28]- [31]. Convolutional neural network (CNN) with machine learning algorithm was also adopted in recent years to classify Mandarin tones [32]- [34]. These newly developed neural networks performed even better comparing to the conventional ANN, with the reported accuracies of around 95% correctness.…”
Section: Introductionmentioning
confidence: 99%